Gambaran Respon Pasien ICU Terhadap Pemasangan Ventilator Mekanik di ICU RSUD RSUD Prof. Dr. Margono Soekarjo - Iwan Purnawan; Eman Sutrisna; Arif Imam Hidayat (Journal of Bionursing, 2020)
Background: One of the reasons a patient is treated in the Intensive Care Unit is respiratory failure. Mechanical ventilator is the last method if other breath assistance models are no longer able to overcome the patient's breathing problems. The installation of a ventilator is one of the stressors of either pain or the process of adaptation of the presence of foreign bodies in the path of his breath. The purpose of this study was to look at the clinical response of patients with mechanical ventilators. Method: This research is a type of quantitative research with a descriptive analytic approach. Respondents involved in this study were 76 patients. The statistical test used is the frequency distribution to see a picture of the patient's response to the installation of a mechanical ventilator. These responses include the ability to adapt to mechanical ventilators and muscle tension. Results: Patient demographic data showed that the average age of patients was 40.7 and the sex was almost the same, 44.7% (male) and 45.3% (female). Almost all respondents showed discomfort response. Only 6.6% (n = 76) showed an adaptation response when viewed from the sound of a mechanical ventilator alarm. Meanwhile, when viewed from muscle tension, all patients who are fitted with a mechanical ventilator show that the muscles are tense and stiff. Conclusion: The installation of a mechanical ventilator has unpleasant effects on the patient.